Kalòs kai agathòs? Government quality and cultural heritage in the regions of Europe - Enrico Bertacchini; Federico Revelli (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper uses panel data on over 200 regions of Europe to study the spatial distribution of UNESCO sites and the capacity of regional governments to conserve heritage, using new designations in the World Heritage List as a proxy. We test whether the location of a region matters by controlling for the stock of World Heritage in the surrounding regions, and if low regional government quality is an obstacle to inclusion of sites into the List. We find some evidence of within-country regional competition for inscription, and of a positive impact of government quality on the chances of having a UNESCO designation.
Keywords: C23; R10; 330; UNESCO World Heritage; quality of government; regions of Europe; spatial; analysis